Balancing acts : reconciling paid work and caregiving among older New Zealanders : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Turitea, New Zealand - Koreshi, Shanika Yoshini (Massey University, 2024)
Population ageing and the rising number of older workers balancing paid work and caregiving responsibilities present significant challenges to social and economic systems. This thesis aims to explore how older New Zealanders, specifically those aged 55 and above, reconcile paid work with caregiving duties and to identify the implications for workforce participation and retirement decisions. Longitudinal data from the New Zealand Health, Work, and Retirement study were used throughout the thesis. The theoretical framework of this thesis is grounded in role theory and the demands-resources approach (Voyandoff, 2005), inspired by Karasek's model (Karasek, 1979). Role theory helps explain how individuals manage multiple roles, such as worker and caregiver, and the demands-resources approach provides a lens to examine how job demands and resources influence the ability to balance these roles. The research is structured around four empirical studies, each addressing distinct aspects of this issue. The first study investigates the predictors of becoming an informal caregiver, focusing on work status preferences and the role of work status incongruence. The findings suggest that older workers in involuntary part-time positions (who prefer more work hours) are more likely to take up caregiving roles compared to those in voluntary part-time or full-time roles. This highlights the importance of aligning work conditions with worker preferences to prevent undue pressure on older adults to assume caregiving roles out of necessity rather than choice. The second study examines the use of flexible work arrangements (FWAs) among older caregivers. It finds that older caregivers utilise more FWAs than their non-caregiving counterparts, particularly in terms of flexible hours, schedules, and time-off arrangements. Self-employed caregivers show a higher likelihood of using these arrangements, indicating the critical role of job autonomy in managing dual responsibilities. The third study explores the impact of work status preferences and FWAs on work-family conflict among older caregivers. The results indicate that certain FWAs, like flexible time-off, can significantly reduce work interference with family for those in involuntary part-time roles, whereas other FWAs do not show the same effect. The fourth study addresses the influence of caregiving and work-related factors on retirement decisions. It reveals that higher caregiving frequency and job stress are significant predictors of retirement among older workers. Additionally, those in involuntary part-time or full-time positions are more likely to retire early compared to those in voluntary full-time roles. Overall, this thesis provides a comprehensive examination of the intersection between paid work and caregiving among older adults in New Zealand. It underscores the critical role that work-related factors play in reconciling paid work and caregiving responsibilities. The findings highlight the importance of aligning work conditions with individual preferences and the need for tailored flexible work arrangements to support older caregivers. These insights will have implications for future research and provide guidance for policymakers and employers aiming to enhance the participation and well-being of older working caregivers in the labour force.
Keywords: Caregiving, Retirement, Older workers, Employment; 350507 Workplace wellbeing and quality of working life; 441009 Sociology of family and relationships